Maintaining Internal Transparency: The Role Of The East Java Province Inspectorate In Realized Accountability In The Financial Sub-Division - Sindi Ratna Bella (Universitas Negeri Yogyakarta, 2025)
The implementation of Transparency and Accountability is a crucial element in creating good governance. These two aspects are interrelated because the East Java Provincial Inspectorate is a supervisory institution that plays a vital role in monitoring and evaluating the performance of local government institutions. However, in this study, the implementation of Transparency covers the internal scope. This study was designed to examine how the East Java Provincial Government Inspectorate maintains Transparency to realise Accountability in the Finance Sub-Section. The method employed in this study is qualitative, with a descriptive approach, where primary data were collected through interviews with treasurers and staff of the Finance Sub-Section. Additionally, secondary data is obtained through a literature review. The results of the study show that the East Java Provincial Inspectorate demonstrates its Transparency by providing access to finance staff to participate in realising accountability in the Finance Sub-Section. Granting access is restricted to finance staff to maintain system security. Although negligence still occurs occasionally, the Finance Sub-Section remains responsible for addressing it.